University Students Perceptions on Entrepreneurship: Commerce Students Attitudes at Lincoln University - Jamal Roudaki (Journal of Accounting, Business and Management (JABM), 2009)
New Zealand is considered the world's top exporter of entrepreneurs and one of three countries with the highest Total Early-Stage Activity (TEA) and Firm Entrepreneurial Activity (FEA) among the 40 countries that Global Entrepreneurship Monitor (GEM) has studied in 2003 (Unitec, 2003-04). It is the responsibility of countrys educational system to sustain such a position through an entrepreneur focused curriculum. Student attitudes and perceptions influence university entrepreneurship education and the promotion of entrepreneurship within New Zealand. Documented research on the attitudes and feelings of university students toward entrepreneurship in New Zealand is rare. This research examines the attitudes of Lincoln University commerce students toward entrepreneurial behaviour factors and the importance of university education to their future entrepreneurial career.